2019
DOI: 10.3390/nu11081754
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Changes in Sodium Content of Selected Popular Commercially Processed and Restaurant Foods: Results from the USDA: CDC Sentinel Foods Surveillance Program

Abstract: This report provides an update from the U.S. Department of Agriculture - Centers for Disease Control and Prevention Sentinel Foods Surveillance Program, exploring changes in sodium and related nutrients (energy, potassium, total and saturated fat, and total sugar) in popular, sodium-contributing, commercially processed and restaurant foods with added sodium. In 2010–2013, we obtained 3432 samples nationwide and chemically analyzed 1654 composites plus label information for 125 foods, to determine baseline labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Other studies show that the results published on canned meat products are minimal compared to fishery products and fresh and processed meat (not canned). Sodium concentrations in samples from other studies were similar to those in our research (Ahuja et al, 2019), even higher in some cases, as in Gillespie et al (2015), where the highest Na concentration was 11590 mg/kg. Bilandžić et al (2021) examined different types of products, including canned meat, where K and Ca concentrations were very similar to those in our work (1932 ± 435 mg/kg and 130 ± 74 mg/kg, respectively).…”
Section: Resultssupporting
confidence: 89%
“…Other studies show that the results published on canned meat products are minimal compared to fishery products and fresh and processed meat (not canned). Sodium concentrations in samples from other studies were similar to those in our research (Ahuja et al, 2019), even higher in some cases, as in Gillespie et al (2015), where the highest Na concentration was 11590 mg/kg. Bilandžić et al (2021) examined different types of products, including canned meat, where K and Ca concentrations were very similar to those in our work (1932 ± 435 mg/kg and 130 ± 74 mg/kg, respectively).…”
Section: Resultssupporting
confidence: 89%
“…Finally, considering the ten-year gap between the time of population sampling and food analysis, we cannot entirely rule out that some changes over time may have occurred towards a sodium reduction and thus partially biased our estimates, especially due to a decrease in salt in processed foods [ 74 ]. Small, though still limited, changes in the sodium content of processed and restaurant foods appear to have occurred in more recent years [ 75 , 76 , 77 ]. However, the relatively low intake of processed and prepackaged foods in the study population, and the evidence that high sodium levels are still found in these products, despite efforts by the food industry in lowering its concentrations [ 78 ] suggests that our assessments are likely still currently valid.…”
Section: Discussionmentioning
confidence: 99%
“…Certain AGEs, such as CML and pyrraline, are likely to form at 120–200 °C [26,27,28]. Some studies [29,30,31,32,33] have reported that the sodium content (expressed as a percentage of mass concentration) ranges between 0.00% and 1.00% in foods, including packaged, commercially processed, and restaurant foods. Therefore, in this study, we used a temperature range of 140–180 °C and a sodium content of 0.00–1.00%.…”
Section: Methodsmentioning
confidence: 99%